Analysis of Secondary Level English Teachers’ Action Research Reports - Puri, Nawaraj; Karki, Tek Mani (KMC Journal, 2023)
Action research (AR) is a methodical process of self-inquiry accomplished by practitioners to unravel work-related problems. This paper analyzed the action research reports (ARRs) in terms of objectives, methodologies, citations and references, structures, areas covered in the problem, and lengths purposively selecting 30 samples of ARRs prepared in the 2020-2021academic year by all the permanent secondary level English teachers of community schools in Nuwakot district. The ARRs were analyzed descriptively by applying document analysis as the method for this study. From this study, 17% of the ARRs were found without clear objectives, 60% ARRs were without the methodological section, and around 77% of ARRs were prepared without in-text citations and references. The variation was found in the ARRs in terms of the format, no research was found in relation to the listening skill, and 23% of ARRs were related to solving writing-related problems. The ARRs were found to have 418 -5312 words in terms of length and the language used especially in the findings were vague. It can be concluded that there is a great variation in the ARRs and a gap between theories and practices of AR in terms of objectives, methodologies, citations and references, structures, and length.